Corrosion study on welded mild stell in soil environment - Mohamed Rais Mohamed
This final year project was focuses on the corrosion behavior at weld metal region and heat affected zone (HAZ) which is known as the highest risk to corrosion attack compare to base metal. The effect of microstructure changes in welded mild steel induced by the processes of arc welding on the pitting and corrosion cracking behaviors was investigated.